Validation of the spiritual and religious attitudes in dealing with illness (SpREUK) in Portuguese Alzheimer's patients. Issue 2 (2nd April 2020) - Pereira, M. G.; Vilaça, M.; Pedras, S.; Vieira, S.; Lima, S.
ABSTRACT: Literature shows that spirituality is a helpful resource for patients to cope with illness, having a positive impact on their quality of life. This study aimed to analyze the psychometric qualities of the Spiritual and Religious Attitudes in Dealing with Illness (SpREUK) using a sample of 128 Portuguese Alzheimer's patients. Results showed that the instrument kept its original factorial structure, with a good adjustment and reliability in all subscales, and associations with quality of life and mindfulness. Therefore, the Portuguese version of the SpREUK has appropriate psychometric properties and is an important resource to assess spirituality in Alzheimer's patients.